Transporte fluviomarítimo e turismo: a viagem à Soure e as perspectivas de desenvolvimento local - MEGUIS, Thiliane Regina Barbosa (Universidade Federal do Pará, 2018)
The main objective of this research was to analyze the importance of the maritime fluvial transport in the tourism and the local development of Soure-PA, and as specific objectives: to analyze the vision of the dynamic agents of the tourist activity on the maritime fluvial transport; to analyze the perception of the users on the maritime fluvio transport to Soure; identify public, private and civil society initiatives to enable tourism and maritime transport; and finally to understand how locomotion occurs within Soure, from a trajectory marked in the relations between the agents that directly influence the actions implemented in the transport service for the locality. As a theoretical-methodological option, the Castells proposed guidelines were followed, exploring its reference in investigations and the concepts of the configuration of a society in networks, but also based on theories that deal with transportation, tourism, interdependence between transport service and tourism, planning and evolution of maritime fluvial transport in the Amazon and Soure. Of qualitative quality, this research was carried out based on exploratory studies, through a combination of bibliographical survey and field research, with systematic observations and semi structured interviews. It was possible to observe that the transportation service is for tourism planning, one of the fundamental elements for the activity to happen. It is the means of locomotion and makes the visitor and the place visited are put in touch, linking different places, contexts and cultures. In this sense, it was noticed that part of the problems experienced by the interviewees in Soure is due to the lack of policies and actions of the public power and the private initiative or even the neglect, in relation to the difficulties that directly affect the user, and which reflect in the tourism. Influencing decisively in the development of Soure, as well as in the competitiveness of the destination, which only happens with the practice of the tourist activity. Therefore, the management of public services requires that articulations of the various social actors take place for the construction of public policies and demand a new perspective social, so that it is possible the occurrence of rights and not needs, because the actors involved are subjects, who must participate in the construction of social reality, thus prevailing relationships between equals.